Speaking and Listening. - Atkinson, Félicia; Bismuth, Julien; Kaplan, Sophie; Sérandour, Yann (s.l. : Shelter Press. La Criée centre d'art contemporain, 2019)
Antin, David ; Bonnet, François J. ; Horvitz, David ; Bismuth, Julien ; Sérandour, Yann ; Lippard, Hanne ; Xatrec, Christian ; Atkinson, Félicia ; Sun Kim, Christine ; Bernstein, Charles ; Kaplan, Sophie
boek